Genetic and Epigenetic Alterations of Brassica nigra Introgression Lines from Somatic Hybridization: A Resource for Cauliflower Improvement - Wang, Gui-xiang; Lv, Jing; Zhang, Jie; Han, Shuo; Zong, Mei; Guo, Ning; Zeng, Xing-ying; Zhang, Yue-yun; Wang, You-ping; Liu, Fan (Frontiers in Plant Science, 2016)
Broad phenotypic variations were obtained previously in derivatives from the asymmetric somatic hybridization of cauliflower ‘Korso’ (Brassica oleracea var. botrytis, 2n = 18, CC genome) and black mustard ‘G1/1’ (Brassica nigra, 2n = 16, BB genome). However, the mechanisms underlying these variations were unknown. In this study, 28 putative introgression lines (ILs) were pre-selected according to a series of morphological (leaf shape and color, plant height and branching, curd features, and flower traits) and physiological (black rot/club root resistance) characters. Multi-color fluorescence in situ hybridization revealed that these plants contained 18 chromosomes derived from ‘Korso’. Molecular marker (65 simple sequence repeats and 77 amplified fragment length polymorphisms) analysis identified the presence of ‘G1/1’ DNA segments (average 7.5%). Additionally, DNA profiling revealed many genetic and epigenetic differences among the ILs, including sequence alterations, deletions, and variation in patterns of cytosine methylation. The frequency of fragments lost (5.1%) was significantly higher than presence of novel bands (1.4%), and the presence of fragments specific to B. carinata (BBCC 2n = 34) were common (average 15.5%). Methylation-sensitive amplified polymorphism analysis indicated that methylation changes were common and that hypermethylation (12.4%) was more frequent than hypomethylation (4.8%). Our results suggested that asymmetric somatic hybridization and alien DNA introgression induced genetic and epigenetic alterations. Thus, these ILs represent an important, novel germplasm resource for cauliflower improvement that can be mined for diverse traits of interest to breeders and researchers.